ERYTHROCYTE MEMBRANE FATTY ACIDS IN MULTIPLE SCLEROSIS PATIENTS AND HOT-NATURE DIETARY INTERVENTION WITH CO-SUPPLEMENTED HEMP-SEED AND EVENING-PRIMROSE OILS - Rezapour-Firouzi, Soheila; Arefhosseini, Seyed Rafie; Ebrahimi-Mamaghani, Mehrangiz; Farhoudi, Mehdi; Baradaran, Behzad; Ali, Torbati Mohammad; Zamani, Fatemeh (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The risk of developing multiple sclerosis (MS) is associated with increased dietary intake of saturated fatty acids. For many years it has been suspected that this disease might be associated with an imbalance between unsaturated and saturated fatty acids. We determined erythrocyte membrane fatty acids levels in Hot nature dietary intervention with co-supplemented hemp seed and evening primrose oils in multiple sclerosis patients. To determine the erythrocyte membrane fatty acids levels and correlate it with expanded disability status scale (EDSS) at baseline after 6 months intervention in MS patients by gas chromatography, in this double blind, randomized trial, 100 RRMS patients with EDSS<6 were allocated into three groups: “Group A” that received co-supplemented hemp seed and evening primrose oils with advised Hot nature diet. “Group B” received olive oil and “Group C” received the co-supplemented oils. The results showed that the mean follow-up was 180±2.9SD days (N=65, 23 M and 42 F aged 34.25±8.07 years with disease duration of 6.80±4.33 years). There was no significant difference in the study parameters at baseline. After 6 months, EDSS, Immunological parameters and the erythrocyte cell membrane with regard to specific fatty acids showed improvement in the group A and C, whereas there was worsening condition for the group B after the intervention. We concluded that Hot-nature dietary intervention with co-supplemented hemp seed and evening primrose oils caused an increase PUFAs in MS patients and improvement in the erythrocyte membrane fatty acids composition. This could be an indication of restored plasma stores, and a reflection of disease severity reduction.